2017
DOI: 10.2174/1381612823666161116125218
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt/mTOR Intracellular Pathway and Breast Cancer: Factors, Mechanism and Regulation

Abstract: Structure and regulation/deregulation of mTOR provides a greater insight into the action mechanism. Also, through this review, one could easily scan first and second generation inhibitors for PI3K/Akt/mTOR pathway besides targeted therapies for breast cancer and the precise role of mTOR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 0 publications
1
77
0
Order By: Relevance
“…Knocking out or inhibiting PTEN has been reported to be able to induce the regenerative abilities of multiple neuronal populations such as corticospinal neurons, dorsal root ganglion, retinal ganglion cells and sensory neurons [37][38][39]. In addition, PTEN also functions as an inhibitor to AKT/mTOR pathway [40], which plays an important role in cell proliferation and survival [41,42]. In AKT/mTOR pathway, phosphoinositide 3-kinases (PI3Ks) convert phosphatidylinositol (4,5)-bisphosphate (PIP2) into phosphatidylinositol (3,4,5)-trisphosphate (PIP3), subsequently activates Akt, mTOR and ribosomal protein (S6), ultimately realizing its neuroprotective effects [43].…”
Section: Discussionmentioning
confidence: 99%
“…Knocking out or inhibiting PTEN has been reported to be able to induce the regenerative abilities of multiple neuronal populations such as corticospinal neurons, dorsal root ganglion, retinal ganglion cells and sensory neurons [37][38][39]. In addition, PTEN also functions as an inhibitor to AKT/mTOR pathway [40], which plays an important role in cell proliferation and survival [41,42]. In AKT/mTOR pathway, phosphoinositide 3-kinases (PI3Ks) convert phosphatidylinositol (4,5)-bisphosphate (PIP2) into phosphatidylinositol (3,4,5)-trisphosphate (PIP3), subsequently activates Akt, mTOR and ribosomal protein (S6), ultimately realizing its neuroprotective effects [43].…”
Section: Discussionmentioning
confidence: 99%
“…mTOR forms two distinct complexes with either raptor (mTORC1) or rictor (mTORC2). mTORC1 acts downstream of the Akt signaling pathway, which is deregulated in approximately 60% of breast cancers and plays critical roles in breast cancer development, progression and resistance to chemotherapeutic drugs [2][3][4][5][6][7][8][9][10][11]. mTORC1 mediates its function via its downstream targets 40S ribosomal S6 kinase (S6K) and 4E-binding protein 1 (4E-BP1) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on the UCA1 expression of gastric cancer cells, we constructed overexpression systems and used silencing lentivirus vectors to investigate the biological function of UCA1 in vitro and in vivo. The PI3K-Akt-mTOR signaling pathway, which is usually abnormal in many human cancers such as pancreatic cancer, colon cancer, breast cancer, and lung cancer [15][16][17][18], was identified as a direct target. Furthermore, our previous studies using microarray screening and bioinformatics analyses to construct the lncRNA-mRNA co-expression network [10], showed that some of the gastric cancer-related mRNAs were co-expressed with UCA1 and were involved in the regulation of the PI3K-Akt-mTOR signaling pathway.…”
Section: Introductionmentioning
confidence: 99%